## Smart Fallacies: i=1, 1= 2 and 1= 3

This mathematical fallacy is due to a simple assumption, that $ -1=\dfrac{-1}{1}=\dfrac{1}{-1}$ . Proceeding with $ \dfrac{-1}{1}=\dfrac{1}{-1}$ and taking square-roots of both sides, we get: $ \dfrac{\sqrt{-1}}{\sqrt{1}}=\dfrac{\sqrt{1}}{\sqrt{-1}}$ Now, as the Euler's constant $ i= \sqrt{-1}$…

subin:Nice work broview comment →

subin:Nice Review!view comment →

UME ACADEMY:We will try this Thankuview comment →

Gaurav Tiwari:Sure & thanks.view comment →

Gaurav Tiwari:Thanks for the input.view comment →